Properties of laminated curves manufactured with steamed veneers from fast-growth tropical wood in Costa Rica - Shirazinia, Mahyar; Moya, Róger; Muñoz, Freddy (Instituto de Ecología, A.C., 2016)
The laminated curves (LC) made with steamed veneers make possible to obtain smaller curvature radius (RC) than when this process is not applied. This research shows the behavior of Alnus acuminata, Tectona grandis, Gmelina arborea, Terminalia oblonga and Swietenia macrophylla –all originated from fast growth plantations– in the manufacture of laminated curves with radios of (4, 6, 8, 10, 12 and 14) cm. The results show that it was possible to reach RC of 4 cm in all species except for T. grandis in which it was only possible to reach RC of 6 cm. The steam process increased the moisture content of the veneer in a range from 3,3% to 10,2%. The adhesive makes possible that bondline for RC smaller than 10 cm do not open, while for RC of 12 and 14 cm the bondline tends to get open (1% as maximum) for all the species. Nevertheless, the bondline opening gets stabilized 4 days after it is fabricated. The veneer deliminations occurred mainly in the interval of RC from 4 to 8 cm. The highest delaminations values take place in the T. grandis and T. oblonga. The shear stress values varied from 7,5 MPa to 11,2 MPa in all tested species. The aging test of adhesive did not alter significantly the shear stress, but delaminating due to the failure of the bondline increased in all species.